2002
DOI: 10.1097/00008877-200209000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cocaine and sucrose withdrawal period on extinction behavior, cue-induced reinstatement, and protein levels of the dopamine transporter and tyrosine hydroxylase in limbic and cortical areas in rats

Abstract: Lever pressing during tests for resistance to extinction and cue-induced reinstatement of cocaine seeking in rats progressively increases over the first 2 months of withdrawal. In the present report, we investigated the generality of these findings in rats trained to self-administer sucrose, a non-drug reinforcer. We also examined whether the time-dependent changes in cocaine seeking correlate with the levels of the dopamine transporter (DAT) and tyrosine hydroxylase (TH) proteins in the amygdala, nucleus accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 50 publications
(61 reference statements)
11
96
2
1
Order By: Relevance
“…While SCM conditioning sessions were restricted to 20 min to avoid satiety and, thus, shorter than cocaine conditioning sessions, the number of responses per session was considerably higher in the SCM than in the cocaine group such that these animals experienced a greater number of reinforcer presentations in the presence of the SCM S + compared to the cocaine S + condition. Nonetheless, as in previous reports where stimuli conditioned to conventional reinforcers were less effective in eliciting reward-seeking than cocaineassociated stimuli (Baptista et al, 2004;Grimm et al, 2002), the SCM S + produced weaker reinstatement than the cocaine S + . Moreover, the SCM S + induced and maintained responding only during the first 10-20 min of the reinstatement test, whereas the cocaine S + produced strong and sustained responding throughout the 60 min session.…”
Section: Discussionsupporting
confidence: 77%
“…While SCM conditioning sessions were restricted to 20 min to avoid satiety and, thus, shorter than cocaine conditioning sessions, the number of responses per session was considerably higher in the SCM than in the cocaine group such that these animals experienced a greater number of reinforcer presentations in the presence of the SCM S + compared to the cocaine S + condition. Nonetheless, as in previous reports where stimuli conditioned to conventional reinforcers were less effective in eliciting reward-seeking than cocaineassociated stimuli (Baptista et al, 2004;Grimm et al, 2002), the SCM S + produced weaker reinstatement than the cocaine S + . Moreover, the SCM S + induced and maintained responding only during the first 10-20 min of the reinstatement test, whereas the cocaine S + produced strong and sustained responding throughout the 60 min session.…”
Section: Discussionsupporting
confidence: 77%
“…Clearly, our electrophysiological recordings support this view. Similar increases in sucrose-seeking behavior have been observed following sucrose abstinence (Grimm et al, 2002). Conversely, we failed to observe similar increased responding or an enhancement in NAc cell firing properties following abstinence from sucrose reinforcement .…”
Section: Cocaine Abstinence Alters Nac Cell Firingsupporting
confidence: 63%
“…Significant studies have shown that cue-induced drug-seeking increases over time during abstinence, leading to the concept of 'incubation of craving' (Grimm et al, 2001). This is a robust phenomenon that has been observed across a number of different drug classes in rats (Di Ciano and Everitt, 2004;Grimm et al, 2002;Shalev et al, 2001;Lu et al, 2007). Moreover, this type of delayed onset craving can be present in human cocaine users (Kosten et al, 2005).…”
Section: Discussionmentioning
confidence: 99%